2018
DOI: 10.1186/s41936-018-0024-8
|View full text |Cite
|
Sign up to set email alerts
|

Influences of olive leaf extract in the kidney of diabetic pregnant mice and their offspring

Abstract: Background: Phytotherapeutic treatment is used in the treatment of diabetes and its complications. The current study aims to evaluate the significant effect of supplementation of aqueous olive leaf extract (OLE) (Olea europaea) in the kidney of diabetic pregnant mice and their fetuses. Forty pregnant mice were divided into four groups contained 10 mice each after mating. The first group was the control (G1). The second group (GII) was intraperitoneally injected by a single dose of (240 mg/kg body weight) of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Inspired by the well-known health benefit of the Mediterranean diet, we hereby assessed the potency of oleuropein, a major phenolic extract of olives that has been shown to be safe to pregnant mice (25), in treating GDM in a genetic modified Lep db/+ (db/+) mouse model. This model harbors a mutated leptin receptor gene Lepr leading to abnormalities closely resembling human GDM symptoms during pregnancy and has been extensively used to evaluate drugs for treating GDM (26).…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by the well-known health benefit of the Mediterranean diet, we hereby assessed the potency of oleuropein, a major phenolic extract of olives that has been shown to be safe to pregnant mice (25), in treating GDM in a genetic modified Lep db/+ (db/+) mouse model. This model harbors a mutated leptin receptor gene Lepr leading to abnormalities closely resembling human GDM symptoms during pregnancy and has been extensively used to evaluate drugs for treating GDM (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, pretreatment of oleuropein at the different doses prevented the formation of these effects. Moreover, Ahmadvand and his co‐workers indicated that oleuropein was able to ameliorate oxidative stress induced renal damages in diabetic rats . This ameliorative property was attributed to the antioxidative and antiatherogenic activities of oleuropein.…”
Section: Introductionmentioning
confidence: 96%
“…Mohammed et al 35 investigated the effects of olive leaf extract on the kidneys of offspring exposed to maternal diabetes and reported a curative effect on kidney functions due to its antioxidant property. Another study reported that OLE (100 and 200 mg/kg) exerted a protective effect against kidney damage caused by unilateral ureteral obstruction through antioxidative, anti-apoptotic, and anti-inflammatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%